Stakeholder engagement in gender and climate change policy processes: Lessons from CCAFS - Mulema, Annet A.; Cramer, Laura K.; Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
With the rapid increase in the dynamics caused by climate change, policies governing climate change have proliferated while the integration of gender considerations to address the gender-differentiated needs and impacts has remained a challenge. Stakeholder engagement is touted as a critical ingredient in climate change decisions and governance at different levels. However, detailed methods and outcomes of gender-responsive stakeholder engagement processes for climate change policy development are rarely published. This paper uses a CCAFS-developed framework of 10 stakeholder engagement principles to examine the stakeholder engagement processes in the gender and climate change policy arena in the context of CGIAR’s Research Program on Climate Change, Agriculture and Food Security (CCAFS). We analyze both primary and secondary data to understand the categories of stakeholders engaged, methods of engagement, and the outcomes and lessons learned across five regions. Our results show that analysis of the existing policies and programs is a very critical entry point for identifying the points of leverage, the type of stakeholders to engage and how to engage them in the processes that focus on integrating gender in climate policies. Working with influential stakeholders, with the capacity and interest to address gender considerations yields more positive results. Mechanisms to address power relations need to be in place for gender considerations to be voiced and integrated and include women in decision-making processes. Co-learning and co-development of knowledge products cultivate interest and commitment among stakeholders to address gender issues, although systematic monitoring and evaluation remains a challenge. This has implications for effective stakeholder engagement in mainstreaming gender in climate policies and evidence-based policy formualation.